A descriptive-contrastive analysis of Hiligaynon and Tagalog noun reduplication patterns - Solis, Marina Tiangha 1937- ([Quezon City s.n.], 1969)
This study is an attempt to find out the similarities and differences of noun reduplication between the two languages with regard to form, meaning, and distribution. The seminar paper is also an attempt to discover the sources of difficulties of Ilongos in learning Tagalog reduplication.
Thesis (M.A.T.Pilipino)--University of the Philippines
Keywords: Hiligaina dialect -- Noun; Tagalog language -- Noun